The Male of Mecynometa Globosa (O. P.-Cambridge) (Araneae, Argiopidae) - Arthur M. Chickering (Psyche: A Journal of Entomology)
The female of this species was described from Guatemala by the elder Pickard-Cambridge in 1889. Apparently it was known only from that part of Central America until Dr. Petrunkevitch reported a female specimen from the Wilcox camp on the San Lorenzo River in Panama in 1925. Mr. Banks reported two females from the Panama Canal Zone in 1929. I now have in my collection about two dozen females from several localities in the Canal Zone and El Valle, Panama. Only three males have appeared in the collection and all were collected in 1934 and 1936. Mecynometa is an interesting genus with a total of seven species now known. Simon described a species from the African Congo; five species have been described from South America; M. globosa (O. P,-Cambridge) is now known from two countries in Central America. Because males have hitherto been unknown I have thought it worth while to describe one of these in this brief paper.